Inositol 1, 4, 5-trisphosphate receptor type 2 is associated with the bone–vessel axis in chronic kidney disease–mineral bone disorder. Issue 1 (31st December 2023) - Xiao, Qiong; Tang, Yun; Luo, Haojun; Chen, Sipei; Tang, Qiao; Chen, Rong; Xiong, Lin; Xiao, Jun; Hong, Daqing; Wang, Li; Li, Guisen; Li, Yi
Abstract: Objective: The pathogenesis of renal osteopathy and cardiovascular disease suggests the disordered bone–vessel axis in chronic kidney disease–mineral bone disorder (CKD–MBD). However, the mechanism of the bone–vessel axis in CKD–MBD remains unclear. Methods: We established a CKD–MBD rat model to observe the pathophysiological phenotype of the bone–vessel axis and performed RNA sequencing of aortas to identify novel targets of the bone–vessel axis in CKD–MBD. Results: The microarchitecture of the femoral trabecular bone deteriorated and alveolar bone loss was aggravated in CKD–MBD rats. The intact parathyroid hormone and alkaline phosphatase levels increased, 1, 25-dihydroxyvitamin D3 levels decreased, and intact fibroblast growth factor-23 levels did not increase in CKD–MBD rats at 16 weeks; other bone metabolic parameters in the serum demonstrated dynamic characteristics. With calcium deposition in the abdominal aortas of CKD–MBD rats, RNA sequencing of the aortas revealed a significant decrease in inositol 1, 4, 5-trisphosphate receptor type 2 (ITPR2) gene levels in CKD–MBD rats. A similar trend was observed in rat aortic smooth muscle cells. As a secretory protein, ITPR2 serum levels decreased at 4 weeks and slightly increased without statistical differences at 16 weeks in CKD–MBD rats. ITPR2 serum levels were significantly increased in patients with vascular calcification, negatively correlated with blood urea nitrogen levels, and positively correlated with serum tartrate-resistant acid phosphatase 5b levels. Conclusion: These findings provide preliminary insights into the role of ITPR2 in the bone–vessel axis in CKD–MBD. Thus, ITPR2 may be a potential target of the bone–vessel axis in CKD–MBD.